Oral administration of lyophilized Dunaliella salina, a carotenoid-rich marine alga, reduces tumor progression in mammary cancer induced rats. Issue 12 (2nd November 2017) - Srinivasan, Ramachandran; Chaitanyakumar, Amballa; Mageswari, Anbazhagan; Gomathi, Ajitha; Pavan Kumar, J. G. S.; Jayasindu, Mathiyazhagan; Bharath, Gunasekaran; Shravan, Jagannathan Sampathkumar; Gothandam, K. M.
Abstract : Dose-dependent effect of Dunaliella salina against breast cancer induced rats. Abstract : Dunaliella salina is a photosynthetic cell factory used for the commercial production of food additives, cattle stock feed and cosmetics as well as active ingredients for pharmaceutical industries. The investigation of the in vivo antitumor activity of D. salina lyophilized powder (DSLP) against 7, 12-dimethylbenz( a )anthracene (DMBA) induced mammary carcinogenesis in female Wistar rats indicated a dose-dependent effect of DSLP. We studied the effect of DSLP at two different dosages of 500 and 1000 mg per kg bw on DMBA induced mammary cancer in rats by measuring the status of antioxidant enzymes, phase I and phase II detoxification enzymes, lipid peroxidation, and glycoconjugated proteins and by investigating the expression pattern of cell proliferation (Ki-67), hormonal receptor (ER, PR and HER2) status by immunohistochemical analysis, and apoptotic (caspase-3 and -9) and pro-inflammatory (COX-2) markers by colorimetric analysis. After 16 weeks of the study, we observed 100% tumor formation (including high tumor incidence and tumor volume) and a significant increase in the level of hormonal receptors, cell proliferation, and pro-inflammatory and apoptosis markers in tumor-bearing animals compared to the control. The oral administration of DSLP (1000 mg per kg bw) to the DMBA treated animals showed up to 83.4% reduction of tumors and effectively restored the levels of biochemical markers in the mammary tissues in addition to the downregulation of the expression of molecular markers. In conclusion, DSLP was found to show a chemopreventive effect against breast cancer induced in rats through the suppression of cell proliferation and the induction of apoptosis.